Геология нефти и газа. Часть 1: электронный курс - Ильина Г. Ф. Галина Фёдоровна; Недоливко Н. М. Наталья Михайловна; Кудряшова Л. К. Лидия Константиновна; Перевертайло Т. Г. Татьяна Геннадьевна; Янкович Е. П. Елена Петровна (Томск, TPU Moodle, 2016)
Заглавие с экрана